2012
DOI: 10.1007/s11255-012-0151-y
|View full text |Cite
|
Sign up to set email alerts
|

Low concentration of heparin used for permanent catheters canal locking is effective and diminishes the risk of bleeding

Abstract: PurposeThere is an increasing number of patients being dialyzed with permanent catheters (PC). In the majority of cases, heparin is used to maintain PC patency. This practice causes clotting disturbances due to heparin leakage and may predispose the patient to bleeding episodes. It has not been well studied whether lowering heparin concentration for canal locking decreases short-term bleeding complications after PC placement.MethodsThis was a prospective single-center randomized open-label trial conducted in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 12 publications
0
11
1
Order By: Relevance
“…Our study contradicts previous publications that showed heparin lock concentrations above 2500 U/mL predispose to early catheter bleeding . Furthermore, it shows that lowering heparin dose below the standard 1000 U/mL dose confers no additional benefit in the first 24–48 h after TDC insertion.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Our study contradicts previous publications that showed heparin lock concentrations above 2500 U/mL predispose to early catheter bleeding . Furthermore, it shows that lowering heparin dose below the standard 1000 U/mL dose confers no additional benefit in the first 24–48 h after TDC insertion.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, Hryszko et al . on evaluation of 75 ESRD patients found that a 2‐h post‐lock APTT to be the only significant and determining factor for acute bleeding . The ability of heparin to leak by as much as 30% (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations